2017
DOI: 10.3389/fpsyg.2017.00127
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different e-Cigarette Generation and Models on Cognitive Performances, Craving and Gesture: A Randomized Cross-Over Trial (CogEcig)

Abstract: Introduction: Most electronic-cigarettes (e-cigarette) are designed to look like traditional cigarettes and simulate the visual, sensory, and behavioral aspects of smoking traditional cigarettes. This research aimed to explore whether different e-cigarette models and smokers' usual classic cigarettes can impact on cognitive performances, craving and gesture.Methods: The study is randomized cross-over trial designed to compare cognitive performances, craving, and gesture in subjects who used first generation el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…This study's nding is similar to a randomized crossed-over control trial, which the researchers explored the effect of different e-cigarette containing 24 mg to 0 mg nicotine. This study demonstrated that there was no signi cant cognitive performance difference between these two different groups (13). It has also been shown that while low doses of nicotine exposure might improve cognitive functions, higher doses could impair cognitive functions.…”
Section: Discussionmentioning
confidence: 52%
“…This study's nding is similar to a randomized crossed-over control trial, which the researchers explored the effect of different e-cigarette containing 24 mg to 0 mg nicotine. This study demonstrated that there was no signi cant cognitive performance difference between these two different groups (13). It has also been shown that while low doses of nicotine exposure might improve cognitive functions, higher doses could impair cognitive functions.…”
Section: Discussionmentioning
confidence: 52%
“…El uso regular de cigarrillos electrónicos con contenido de nicotina conduce a una dependencia de la nicotina (Case et al, 2018;Hammond et al, 2021), y los fumadores cambian al tabaco para obtener más nicotina rápidamente (Grana, Benowitz y Glantz, 2014;O'Connell et al, 2019). El hecho de que incluso los cigarrillos electrónicos sin nicotina aumentaran el consumo posterior de cigarrillos convencionales puede explicarse porque ambos comparten el mismo mimetismo, es decir, movimientos de mano a boca, inhalación y exhalación de humo (Caponnetto et al, 2013(Caponnetto et al, , 2017Park et al, 2020).…”
Section: Discussionunclassified
“…Of the studies included in this review, two studies included adolescent and young adult participants (Wade et al 2022;Xie et al 2020a), while the rest recruited adult participants only (Caponnetto et al 2017;Hobkirk et al 2018;MacLean et al 2021;Dawkins et al 2013; Kim et al (1) first generation e-cigarette (24 mg nicotine)…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…(3) e-cigarette (12 mg nicotine) and told e-cigarette did not contain nicotine (4) e-cigarette (0 mg nicotine) and told e-cigarette did not contain nicotine 2022a, b; Xie et al 2020b). The majority of studies (n = 6) included participants who were either current smokers only (Caponnetto et al 2017;MacLean et al 2021;Dawkins et al 2012;Dawkins et al 2013;Kim et al 2022a), or e-cigarette users with a history of cigarette smoking (Palmer and Brandon 2019). Another study included only participants with a history of e-cigarettes and vaping e-liquid containing nicotine (Hobkirk et al 2018).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%